Digital Front End Technology for Long-Distance Power Line Communication - Hongjian GAO; Hongwei XIE; Xu LU; Yao LIU; Lijun ZHANG; Yang CAO (Zhongguo dianli)
Since the power line communication (PLC) channel is not specifically designed for communication, there usually exists a large noise and/or a strong interference around the frequency band of a PLC system. It is not economical to change the structure of the analog front end (AFE) to improve the performance of the PLC system. Therefore, based on the equivalent complex baseband and Nyquist windowing technology, a new digital front end (DFE) structure is proposed. The windowing at the receiver end can not only effectively suppress the out-of-band narrowband interference and eliminate the impact of adjacent frequency PLC systems or wireless systems, but also reduce the complexity of the AFE and save design costs. The simulation results show that the Nyquist windowing is better for concentrating the energy of narrowband interference to the less subcarriers, which is convenient for detection and elimination of the narrowband interference, thus improving the performance of the system. In addition, the effectiveness of the proposed DFE technology is further verified through field tests.